Media Relations Strategy of PT Panca Amara Utama in Responding to Workforce Recruitment Issues - Maria Ulfa; Asriana Syamsudin (Jogjakarta Communication Conference (JCC), 2026)
Media relations is a part of public relations that has a crucial function within a company, namely building relationships with mass media with the aim of maintaining the company’s image and increasing public trust. The purpose of this study is to identify the media relations strategies of PT Panca Amara Utama in responding to workforce recruitment issues that have been widely reported on social media. This research uses a qualitative-descriptive approach by describing events as they occur. The results of this study show that there are several media relations strategies implemented by PT Panca Amara Utama in responding to workforce issues, including media monitoring, mass media management, rapid response through internal meetings, and strengthening the company’s image through coverage of Corporate Social Responsibility (CSR) programs.